Comparative histopathology of the estrous or menstrual cycle in laboratory animals - Sato, Junko (Japanese Society of Toxicologic Pathology, 2016)
Accurate analysis of female reproductive toxicity requires a thorough understanding the differences in and specifics of estrous or menstrual cycles between laboratory animals. There are some species differences such as the time of sex maturation, the length of the estrous or menstrual cycle, the length of the luteal phase, the number of dominant follicles or corpora lutea, the size of follicles, processes of luteinization, and hormonal changes during the estrous or menstrual cycle. Rodents have a short estrous cycle, and their ovarian cycling features are the same in both ovaries, which contain a large number of follicles and corpora lutea. The dog estrous cycle is much longer than those of other laboratory animals, and it includes a long anestrus phase. The duration of the menstrual cycle of monkeys is roughly 30 days, and their ovarian cycling features are different between the left and right ovaries. In both rodents and dogs, the theca cells invade the early luteum, mixing with granulosa cells during luteinization. However in monkeys, the theca layer dose not mix with the granulosa cells as it invaginates only slightly into the early luteum. In addition, we found that high progesterone levels after ovulation are sustained for a much shorter duration in rodents than in dogs and monkeys due to the comparatively rapid passage of the rodent luteal phase. Based on these species differences, animal species for use in ovarian toxicology studies need to be selected appropriately.